Model Manajemen Penyimpanan Data Berbasis Pipeline Produksi Film Animasi 3D: Pipeline-Based Data Storage Management Model for 3D Animation Film Production - Yuniawan, Aryanto; Sa`di, Ahmad; Anggono, Eko Tri (Jurnal Pendidikan Sains dan Komputer, 2026)
The 3D animated feature film industry generates a large and diverse volume of digital data due to the complexity of its production pipeline, which spans multiple stages and departments. Each stage of the production pipeline, from pre-production to post-production, generates data with distinct characteristics, access patterns, and importance levels. However, in practice, data storage management is often carried out uniformly, without consideration of its relationship to the production flow. This study aims to develop a data storage managementmodel grounded in the production pipeline of the 3D animated feature film industry. The study uses a descriptive approach, supported by applied modeling, and draws on observations, interviews, and documentation from the 3D animation production environment. The model is developed by identifying production pipeline stages, classifying data types (production, non-production [organizational operations], backup, and archive), and analyzing access characteristics and data storage needs. The results show that the proposed model can map the relationships among production pipeline stages, data types, and appropriate storage strategies, thereby forming a more systematic and contextual data management framework. The implementation of the model in a 3D animation production case study shows that adjusting storage strategies based on the production pipeline and data characteristics is realistic and applicable. This model is expected to serve as a reference for managing data storage in the production environments of 3D widescreen animated films.